2018
DOI: 10.1039/c7ra12629h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of byproducts formation in the isobutane/butene alkylation on HY zeolites

Abstract: Submicron-size HY zeolites with a particles size of 200–700 nm were synthesized employing a crystal precipitation method in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…It is generally found that catalysts with strong Brønsted sites are more efficient for the alkylation reaction than oligomerization. 51 Other parameters, such as the spatial distribution of activity within catalyst particles, mass transfer, diffusional limitation, and intraparticle heat effects, were also discussed. Although alkylation processes based on solid acids are not operational so far, some companies have developed processes (see Table 4).…”
Section: Recent Progress On Solid Acid Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally found that catalysts with strong Brønsted sites are more efficient for the alkylation reaction than oligomerization. 51 Other parameters, such as the spatial distribution of activity within catalyst particles, mass transfer, diffusional limitation, and intraparticle heat effects, were also discussed. Although alkylation processes based on solid acids are not operational so far, some companies have developed processes (see Table 4).…”
Section: Recent Progress On Solid Acid Catalystsmentioning
confidence: 99%
“…62 Fortunately, the deactivation of zeolites was reversible and could be entirely recovered by several treatments; for example, coked zeolite is regenerated by both partial liquid-phase hydrogenative treatment at reaction conditions and complete liquid-phase hydrogenative regeneration at high temperature, as hydrogen was shown to be very effective for the regeneration of the catalysts. 63,64 Y zeolites are the most studied catalysts for alkylation, 51 as they proved to be less prone to deactivation than other types of zeolites such as zeolite X, mordenite, ZSM, and MCM-1 and showed high selectivity to isooctane. Nevertheless, the alkylation efficiency of some zeolites such as LaY was not satisfactory because of the short lifespan of the zeolite and low selectivity to isooctane.…”
Section: Recent Progress On Solid Acid Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The olefin then obtains H + from the catalyst surface to form a carbocation, and the carbocation preferentially breaks into a small molecular hydrocarbon containing primary and secondary carbon ions at the β position, and then isomerized to a more stable tertiary carbon ion. [88] Finally, the stable tertiary carbon ion returns H + to the catalyst, and turns itself into an olefin and other more useful hydrocarbons. [89] Fig.…”
Section: Catalytic Cracking Mechanismmentioning
confidence: 99%
“…High I/O ratio is usually adopted to inhibit the oligomerization of olens, especially when xed bed reactor is used. 16,17,28 With higher I/O ratio, the olen concentration around the catalytic center is lower, inhibiting the further reaction of alkyl carbocations with other olens which forms undesired heavier products. [29][30][31] There are many advantages of increasing the I/O ratio, but this is mainly achieved by enhancing the I/O ratio in feed and the recycle of isobutane is inevitable, which largely increases operating cost.…”
Section: Introductionmentioning
confidence: 99%